2015
DOI: 10.1016/j.jaapos.2015.07.151
|View full text |Cite
|
Sign up to set email alerts
|

High specificity of the pediatric vision scanner in a private pediatric primary care setting

Abstract: Purpose-To determine the specificity of the Pediatric Vision Scanner, a binocular retinal birefringence scanner, in its intended setting, a pediatric primary care office.Methods-A total of 102 preschool children (age 2-6 years) were screened during a well-child pediatric visit using the Pediatric Vision Scanner and the SureSight Autorefractor and completed a masked comprehensive pediatric ophthalmic examination (gold standard examination).Results-Based on the gold standard examination, one child had anisometro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Sixteen fair-quality studie s (16 7 12 obser vations) evaluated autorefractors (eTables 6-17 in the Supplement). 49,51,55,57,58,65,66,70,[72][73][74]77,78,84,88,91 Overall, most studies found moderate positive LRs and small negative LRs, although some found large positive and negative LRs.…”
Section: Accuracy Of Screening Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen fair-quality studie s (16 7 12 obser vations) evaluated autorefractors (eTables 6-17 in the Supplement). 49,51,55,57,58,65,66,70,[72][73][74]77,78,84,88,91 Overall, most studies found moderate positive LRs and small negative LRs, although some found large positive and negative LRs.…”
Section: Accuracy Of Screening Testsmentioning
confidence: 99%
“…70,91 About one-third of the studies included participants younger than 3 years. 48,56,65,66,71,72,[75][76][77]80,81,85,88,91 The included studies reported accuracy of tests for a variety of target conditions, ranging from very specific (eg, astigmatism) to broad (eg, amblyopia risk factors). The prevalence of target conditions was generally much higher in samples from ophthalmology clinics 53,56,57,62,66,68,69,72,75,77,80,81,85,88 than in those from primary care, community, Head Start, or school settings.…”
Section: Accuracy Of Screening Testsmentioning
confidence: 99%
“…1). In a pair of studies, 400 preschool children were screened using a prototype retinal birefringence scanner that collected five scans in 2.5 s from children aged 2-6 years old at two pediatric ophthalmology private practices and at one pediatric primary care practice [18,19]. Screening results were compared with findings at a gold standard comprehensive examination by a pediatric ophthalmologist who was masked to screening results.…”
Section: Binocular Retinal Birefringence Screeningmentioning
confidence: 99%
“…Testing can be completed in 10 s in children as young as 2 years of age. Thus far, the ability of the PVS to detect amblyopia and strabismus has been promising (Loudon et al, 2011; Jost et al, 2014; Jost et al, 2015). While the device was originally designed to assess strabismus, it has been hypothesized that the PVS also detects amblyopia because, similar to strabismic patients, amblyopic patients also have inaccurate and/or unstable fixation (Loudon et al, 2011; Gonzalez et al, 2012; Jost et al, 2015).…”
Section: Screening Toolsmentioning
confidence: 99%